2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Demographics on the Spatial Visualization Skills in 2D and 3D Course Offerings

Abstract: This paper reports on the impact that demographic characteristics have in the development of spatial visualization skills on two different offerings of CAD-related courses at two different institutions. The ultimate objective of this information is to identify factors that might be influencing visualization skills development. The importance placed on visualization skills improvement is due to the fact that they have been related to expected performance by students in the technical fields. The data for this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…An early study from I. M. Smith in 1964 [6] identified at least 84 career areas for which spatial skills are important. Women, underrepresented minorities, and non-traditional students have been found to have somewhat lower spatial visualization skills affecting their performance in STEM fields but after specialized training, they showed improvements in their skills [7] - [10]. A study by Uttal, et al [11] published in 2013 found that more than 200 studies on improvement of spatial skills demonstrated that students who receive extensive training and practice on spatiallyrelevant skills showed increased visualization skills.…”
Section: Introductionmentioning
confidence: 99%
“…An early study from I. M. Smith in 1964 [6] identified at least 84 career areas for which spatial skills are important. Women, underrepresented minorities, and non-traditional students have been found to have somewhat lower spatial visualization skills affecting their performance in STEM fields but after specialized training, they showed improvements in their skills [7] - [10]. A study by Uttal, et al [11] published in 2013 found that more than 200 studies on improvement of spatial skills demonstrated that students who receive extensive training and practice on spatiallyrelevant skills showed increased visualization skills.…”
Section: Introductionmentioning
confidence: 99%